Persisting burden and challenges of rheumatic heart disease. (15th July 2021) - Marijon, Eloi; Mocumbi, Ana; Narayanan, Kumar; Jouven, Xavier; Celermajer, David S
Abstract: Rheumatic heart disease (RHD) is the result of episodes of acute rheumatic fever with valvular (and other cardiac) damage caused by an abnormal immune response to group A streptococcal infections, usually during childhood and adolescence. As a result of improved living conditions and the introduction of penicillin, RHD was almost eradicated in the developed world by the 1980s. However, being a disease of poverty, its burden remains disproportionately high in the developing world, despite being a fundamentally preventable disease. Rheumatic heart disease generates relatively little attention from the medical and science communities, in contrast to other common infectious problems (such as malaria, HIV, tuberculosis), despite the major cardiovascular morbidity/mortality burden imposed by RHD. This relative neglect and paucity of funding have probably contributed to limited fundamental medical advances in this field for over 50 years. Given the importance of prevention before the onset of major valvular damage, the main challenges for RHD prevention are improving social circumstances, early diagnosis, and effective delivery of antibiotic prophylaxis. Early identification through ultrasound of silent, subclinical rheumatic valve lesions could provide an opportunity for early intervention. Simple echocardiographic diagnostic criteria and appropriately trained personnel can be valuable aids in large-scale public health efforts. In addition, a better understanding of the immunogenic determinants of the disease may provide potential routes to vaccine development and other novel therapies. Graphical Abstract: